2020
DOI: 10.1108/jabes-11-2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

GST fraud prevention to ensure business sustainability: a Malaysian case study

Abstract: PurposeThis study provides in-depth explanation of Goods and Services Tax (GST) fraud prevention towards sustainability business.Design/methodology/approachThis study applies a qualitative research method, i.e. case study, to address the specific research objective.FindingsThe finding revealed a GST prevention model towards sustainable business. The finding shows that it is pertinent for the government to set preventive strategies in order to retain sustainable income for the government. Two essential dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…The purpose of this article is to determine whether macroeconomic uncertainty can be used to explain and forecast crude oil futures market volatility. The empirical findings in this study provide compelling evidence of macroeconomic uncertainty variables’ influence and predictability on crude oil volatility (Agyekum et al 2021 ; Othman et al 2020 ; Zhang et al 2021 ).…”
Section: Resultsmentioning
confidence: 54%
“…The purpose of this article is to determine whether macroeconomic uncertainty can be used to explain and forecast crude oil futures market volatility. The empirical findings in this study provide compelling evidence of macroeconomic uncertainty variables’ influence and predictability on crude oil volatility (Agyekum et al 2021 ; Othman et al 2020 ; Zhang et al 2021 ).…”
Section: Resultsmentioning
confidence: 54%
“…Zhang et al ( 2019a ) explain that under the situation of carbon regulations, it is quite challenging to deal with the operational strategies. Green innovation is something like a hybrid system to handle the CO2 emission (Antoni et al 2020 ; Muller and de Klerk 2020 ; Othman et al 2020 ; Vermeulen et al 2020 ; Zhang et al 2019a ). White and van Koten ( 2016 ) explore the linkage between the socio-ecological innovation and carbon emission.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This study found that green growth has a positive association with the environmental condition of the country and is similar to the results of (Chien et al, 2021b) and Chien, Kamran, et al (2021), who also exposed that green finance, such as renewable energy, has a positive impact on the environmental conditions. In addition, the results also exposed that the environmental-related tax significantly improves the environmental condition of the country, and this matched with the outcomes of (Othman et al, 2020), who also found that the environmental-related measures have a positive impact on the environmental condition of the country. Lastly, the results also unveiled that eco-innovation was significantly related to the environmental conditions, which is in line with the results of (Chien et al, 2021d), who also discovered that innovation in technology could play a positive role on Table 6 Granger causality in quantile test results.…”
Section: Discussion Conclusion and Policy Implicationssupporting
confidence: 66%